Ensemble machine learning prediction of posttraumatic stress disorder screening status after emergency room hospitalization. (December 2018) - Papini, Santiago; Pisner, Derek; Shumake, Jason; Powers, Mark B.; Beevers, Christopher G.; Rainey, Evan E.; Smits, Jasper A.J.; Warren, Ann Marie
Highlights: A substantial minority of emergency room admits develop posttraumatic stress disorder. Efficient and reliable prospective prediction of PTSD can facilitate early intervention. Machine learning yielded good prediction of future PTSD screening status using minimally invasive data. Abstract: Posttraumatic stress disorder (PTSD) develops in a substantial minority of emergency room admits. Inexpensive and accurate person-level assessment of PTSD risk after trauma exposure is a critical precursor to large-scale deployment of early interventions that may reduce individual suffering and societal costs. Toward this aim, we applied ensemble machine learning to predict PTSD screening status three months after severe injury using cost-effective and minimally invasive data. Participants ( N = 271) were recruited at a Level 1 Trauma Center where they provided variables routinely collected at the hospital, including pulse, injury severity, and demographics, as well as psychological variables, including self-reported current depression, psychiatric history, and social support. Participant zip codes were used to extract contextual variables including population total and density, average annual income, and health insurance coverage rates from publicly available U.S. Census data. Machine learning yielded good prediction of PTSD screening status 3 months post-hospitalization, AUC = 0.85 95% CI [0.83, 0.86], and significantly outperformed all benchmark comparison models in a cross-validation procedure designed to yield an unbiased estimate of performance. These results demonstrate that good prediction can be attained from variables that individually have relatively weak predictive value, pointing to the promise of ensemble machine learning approaches that do not rely on strong isolated risk factors.